The Potential of Flavonoid Compounds in Wet Organic Waste as Antibacterial Agents: A Critical Approach to Waste Management Innovation Toward a Circular Economy - Faiha Talita Zahirah; Halla Syaima Nabilah; Adeline Aurelia Syaira; Zahra Syifa Alhaya; Amirah Nur Azkia; David Bahrin (Ali Institute of Research and Publication, 2026)
Flavonoid compounds are natural polyphenolic bioactive compounds known to possess significant biological and antibacterial activities, as well as added value. These compounds have the ability to inhibit the growth of pathogenic bacteria that can cause health disorders in humans. Since flavonoids cannot be produced by the human body, their sources must be obtained from food, beverages, or other external sources. Wet organic waste, such as fruit peels, vegetable scraps, and agricultural waste, is reported to still contain flavonoid compounds in varying amounts, depending on the type of waste. By employing a systematic literature review (SLR) method on previous studies published in indexed national and reputable international journals, the potential of flavonoid compounds in wet organic waste can be evaluated. This includes their mechanism of action, factors influencing the effectiveness of their antibacterial activity, and their relevance to human health. The results of the review indicate that flavonoid compounds derived from wet organic waste are capable of inhibiting Gram-positive and Gram-negative bacteria commonly associated with infections, such as Staphylococcus aureus and Escherichia coli. Factors such as the type of waste material, extraction method, and extract concentration influence the effectiveness of the flavonoids' antibacterial activity. Furthermore, the utilization of flavonoids from organic waste aligns with the circular economy paradigm in supporting sustainable waste management. It can be concluded that flavonoids from wet organic waste hold great potential as natural antibacterial agents that support human health while simultaneously providing an innovative solution for sustainability-based waste management.